Activated Neutrophils Secrete Chitinase-Like 1 and Attenuate Liver Inflammation by Inhibiting Pro-Inflammatory Macrophage Responses - Lu, Yu; Chang, Na; Zhao, Xinhao; Xue, Renmin; Liu, Jing; Yang, Lin; Li, Liying (Frontiers in Immunology, 2022)
Excessive activation and recruitment of neutrophils are generally considered to be associated with pathological aggravation of multiple diseases. However, as the role of neutrophils in tissue injury repair is receiving increasing attention, it is necessary to further explore the beneficial role of activated neutrophils in promoting the resolution of inflammation after injury. In this study, we found that activated neutrophils have a crucial function in suppressing liver inflammation. In methionine-choline-deficient and high-fat (MCDHF) diet induced liver inflammation in mice, tail vein injection of activated neutrophils (A-Neu, stimulated by sphingosine 1-phosphate) inhibited the expressions of pro-inflammatory cytokines in the liver, including C-C chemokine motif ligand4, tumor necrosis factor and nitric oxide synthase 2, and attenuated liver injury. However, non-activated neutrophils (N-Neu) did not have these effects. In vitro, pro-inflammatory macrophages were co-cultured with N-Neu or A-Neu by transwell, respectively. A-Neu was found to suppress the pro-inflammatory phenotype of macrophages by using RT-qPCR, western blot and cytometric bead array. Microarray analysis showed that there were systematic variations in transcript expression levels between N-Neu and A-Neu. GeneVenn software was used to show the gene expression overlap between GO terms including Regulation of Cell Communication, Cytokine Secretion, Inflammatory Response and Extracellular Space clusters. We identified that Chitinase-like 1 (CHIL1) secreted by S1P activated neutrophils may be an important mediators affecting the pro-inflammatory macrophage responses. In the injured liver of mice induced by MCDHF diet, the expression of Chil1 mRNA increased and was positively correlated with the neutrophil marker Ly6g. Moreover, the secretion of CHIL1 in A-Neu increased significantly. Strikingly, the effect of A-Neu on macrophage response was reproduced by incubating pro-inflammatory macrophages with recombinant CHIL1. A-Neu conditioned medium were incubated with CHIL1 antibody-conjugated protein G beads, magnetically separated to immunodepletion CHIL1 from the A-Neu supernatant, which can partially weaken its inhibitory effect of A-Neu on the production of macrophage pro-inflammatory cytokines. Together, the conclusions indicated that A-Neu could inhibit the pro-inflammatory macrophage responses by secreting CHIL1, thereby effectively inhibiting liver inflammation.